The ritual [videorecording (DVD)] - Midell, Dave; Natale, Enrico, 1982-; Natale, Enrico, 1982-; Pacino, Al, 1940-; Stevens, Dan, 1982-; Greene, Ashley, 1987-; Cowen, Abigail, 1998-; Giraldo, Maria Camila; Williams, Meadow, 1966-; Allen, Courtney Rae; Pattison, Liann; Fabian, Patrick; et al. (Decal Releasing, LLC, 2025)
"The harrowing true story of the exorcism of Emma Schmidt. Two priests--one questioning his faith and one reckoning with a troubled past--must work together to preform a series of terrifying exorcisms to save the young woman's soul."--